Structural, Morphological, and Optical Properties of Nano- and Micro-Structures of ZnO Obtained by the Vapor–Solid Method at Atmospheric Pressure and Photocatalytic Activity - Carlos Bueno; Adan Luna; Gregorio Flores; Héctor Juárez; Mauricio Pacio; René Pérez; Javier Flores-Méndez; David Maestre; Raúl Cortés-Maldonado (Crystals)
Micro- and nano-structures of ZnO were synthesized by the vapor–solid method at 600, 700, and 800 °C in atmospheres of Ar and air, at atmospheric pressure. The structural characterization XRD shows that the nano-structures synthesized in air atmosphere at 600 °C, while diffraction peaks were found due to Zn because the presence of metallic Zn remains on the surface of the pellet. SEM images show that the morphologies range from nano-wires to micro-tubes. When cathodoluminescence is measured in micro-tubes, there is a shift of the near-band edge of the ZnO toward red; this is due to structural defects in the ZnO network. This result is corroborated with panchromatic CL measurements, which exhibit a difference in brightness between the micro-tubes. Furthermore, EDS measurements show an atomic quantity ratio of Zn:O that differs from the stoichiometric composition in the micro-tubes. The photocatalytic activity of three types of structures—nano-wires, micro-tubes, and micro-rods under UV irradiation using methylene blue as a model pollutant—were evaluated. The best response was obtained for nanowires, not only because they have a larger surface area but also because of the present defects.